2022
DOI: 10.1111/hae.14675
|View full text |Cite
|
Sign up to set email alerts
|

Association of factor expression levels with annual bleeding rate in people with haemophilia B

Abstract: Introduction: Gene therapy clinical trials measure steady-state clotting factor expression levels (FELs) to evaluate the modulation of the bleeding phenotype, aiming to offer consistent protection against breakthrough bleeding events. The link between FELs and bleeding risk in people with haemophilia B (PwHB) is not well understood. Aim:We evaluated the association between FEL and ABR in PwHB. Methods:This cross-sectional study extended the CHESS burden of illness studies in Europe and the United States. Recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…Real‐world outcomes of PWHB in Europe and the Unites States saw that, when receiving standard half‐life ( n = 114) or EHL ( n = 36) FIX replacement products, only 19% and 32% of PWHB, respectively, experienced no bleeds in the previous year, suggesting the occurrence of breakthrough bleeds in some PWHB 16 . Further to this, a recent study of PWHB in Europe and the Unites States ( N = 407) demonstrated that increases in FIX expression levels were significantly associated with decreases in annualized bleeding rate; for every 1% increase in FIX expression levels, the average annualized bleeding rate decreased by 0.08 ( p < .001) 17 . To achieve higher factor trough levels, PWHB may need to infuse factor replacement products more frequently or use higher doses.…”
Section: Existing Challenges In the Clinical Management Of Hbmentioning
confidence: 71%
See 1 more Smart Citation
“…Real‐world outcomes of PWHB in Europe and the Unites States saw that, when receiving standard half‐life ( n = 114) or EHL ( n = 36) FIX replacement products, only 19% and 32% of PWHB, respectively, experienced no bleeds in the previous year, suggesting the occurrence of breakthrough bleeds in some PWHB 16 . Further to this, a recent study of PWHB in Europe and the Unites States ( N = 407) demonstrated that increases in FIX expression levels were significantly associated with decreases in annualized bleeding rate; for every 1% increase in FIX expression levels, the average annualized bleeding rate decreased by 0.08 ( p < .001) 17 . To achieve higher factor trough levels, PWHB may need to infuse factor replacement products more frequently or use higher doses.…”
Section: Existing Challenges In the Clinical Management Of Hbmentioning
confidence: 71%
“…16 Further to this, a recent study of PWHB in Europe and the Unites States (N = 407) demonstrated that increases in FIX expression levels were significantly associated with decreases in annualized bleeding rate; for every 1% increase in FIX expression levels, the average annualized bleeding rate decreased by 0.08 ( p < .001). 17 To achieve higher factor trough levels, PWHB may need to infuse factor replacement products more frequently or use higher doses. The recent international consensus recommendations for PWHB go beyond this, identifying how recommendations have been extrapolated from pharmacokinetic (PK) data on PWHA.…”
Section: Phenotypic Differences and Trough Levelsmentioning
confidence: 99%
“…5-10 IU/dL are associated with substantial reductions in bleed risk, while activity levels >25 IU/dL may be necessary to prevent all bleeding events for some products. 73 Fluctuating plasma activity levels during FIX prophylaxis are also a consideration when managing bleed risk. 72 For some patients, peak plasma activity levels and/or time above trough are more relevant than minimum trough levels.…”
Section: Clinical Perspective On Ehl Prophylaxismentioning
confidence: 99%
“…However, even higher levels may be needed. Recent analyses indicate factor activity levels consistently in the range of 5–10 IU/dL are associated with substantial reductions in bleed risk, while activity levels >25 IU/dL may be necessary to prevent all bleeding events for some products 73 …”
Section: Expert Opinionmentioning
confidence: 99%
“…1 4 With the use of clotting factor concentrates, some patients still experience breakthrough bleeds due to variable, often suboptimal, trough levels according to the lifestyle of the patients and schedule of treatment. 1 4 5 6 7 This of course increases the risk of the development of arthropathy, which negatively influences lifestyle and quality of life. 1 8 Recent developments have led to extended half-life products using techniques like PEGylation, Fc fusion, and albumin fusion, which improve stability and reduce infusion frequency.…”
mentioning
confidence: 99%